2004
DOI: 10.1080/10284150412331281031
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and REM-sleep Deprivation Modulate in Rats the Impairment of Spreading Depression by a Single Sub-convulsing Dose of Pilocarpine

Abstract: This study aimed to investigate the effect of a single injection of pilocarpine upon the phenomenon of cortical spreading depression (SD), in adult rats submitted to early malnutrition and/or to REM-sleep deprivation for 72h prior to the SD-recordings. The SD was recorded continuously for 3-4h in 13 well-nourished (W) and 15 early-malnourished (M) adult rats. One to two hours after the beginning of the recording session, a sub-convulsing intraperitoneal (i.p.) injection of pilocarpine (190mg/kg) was applied an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…17,18 As we have previously demonstrated in laboratory animals, drugs used with therapeutic purposes in neurological diseases present distinct effectiveness as a function of the nutritional status of the organism. 23,35,36 In line with the above evidence, we found that early malnutrition enhanced the antagonistic effects of lithium on CSD. These findings collectively indicate that the responsiveness of the CSD to distinct compounds may not be the same for all types of pharmacological substances.…”
Section: Lithium/nutrition Interaction On Csdsupporting
confidence: 88%
“…17,18 As we have previously demonstrated in laboratory animals, drugs used with therapeutic purposes in neurological diseases present distinct effectiveness as a function of the nutritional status of the organism. 23,35,36 In line with the above evidence, we found that early malnutrition enhanced the antagonistic effects of lithium on CSD. These findings collectively indicate that the responsiveness of the CSD to distinct compounds may not be the same for all types of pharmacological substances.…”
Section: Lithium/nutrition Interaction On Csdsupporting
confidence: 88%
“…The possible relationship between CSD and brain excitability has been investigated in our laboratory using the acute pilocarpine administration paradigm; both convulsing (Guedes and Cavalheiro, 1997) and sub-convulsing dosing with a single injection of pilocarpine (Vasconcelos et al, 2004; Guedes and Vasconcelos, 2008) decelerated CSD. In the present study, we treated young animals (PND35) over 21 days with a sub-convulsing dose of pilocarpine and confirmed its CSD decelerating action.…”
Section: Discussionmentioning
confidence: 99%
“…Slow wave sleep is also associated with reductions in brain temperature and metabolic demand for oxygen and glucose, as well as replenishment of ATP and glycogen stores (Aalling et al, 2018;Caporale et al, 2021). REM sleep deprivation decreases the threshold for cortical spreading depressions which are found frequently after acquired brain injuries and thought to contribute to secondary brain injury (De Vasconcelos et al, 2004;Levesque et al, 2021). Interestingly, a recent study of analgesia and sedation after a variety of brain injuries found that benzodiazepine treatment increased the incidence of cortical spreading depressions (Hertle et al, 2012).…”
Section: Sleeping With One Eye Open Sleep Architecture Is Disrupted During Critical Illnessmentioning
confidence: 99%